Synthesis of dimethyl‐ and diphenylsilane‐based oligo(azine)s: Thermal, optical, electronic, and morphological properties. Issue 38 (28th July 2022) - Sobarzo, Patricio A.; Jessop, Ignacio A.; Pérez, Yasmín; Hauyon, René A.; Velázquez‐Tundidor, María V.; Medina, Jean; González, Alexis; García, Luis E.; González‐Henríquez, Carmen M.; Coll, Deysma; Ortiz, Pablo A.; Tundidor‐Camba, Alain; et al.
Abstract: Four new oligo(azine)s were synthesized from dimethyldiphenylsilane and tetraphenylsilane core‐based dialdehydes and hydrazine by high‐temperature polycondesation and proposed as materials for optoelectronic applications. The oligo(azine)s were characterized by EA, FT‐IR, and NMR. Although most of samples were poorly soluble, TPS‐containing PAZ‐4 was soluble in aprotic polar solvents. According to SEC and FT‐IR studies, the samples were oligomers with up to five repeating units long. TGA showed highly stable samples with TDT10% over 420°C except for PAZ‐1 that contains a DMS core along with phenyl units, and thus, the lowest carbon content in the series. From DSC analysis, the substitution of phenyl groups in PAZ‐1/3 by biphenyl moieties in PAZ‐2/4 allowed to obtain oligo(azine)s with lower T g values. PAZ‐4 showed a UV‐A absorption with optical band‐gap values of 2.91 and 2.65 eV from UV–vis (solution) and DRS (films), respectively. PL analysis showed a violet emission. PAZ‐4 showed resistivity of 29.24 Ω cm, similar to wide‐band gap materials. Their contact angle measurements showed a critical surface tension of 42.29 dynes/cm, revealing its hydrophobicity. AFM analysis indicated that the PAZ‐4 films had homogeneous surfaces. Young's modulus close to 4.46 GPa was established by microindentation for the PAZ‐4 thin‐films. Abstract :